2015
DOI: 10.4081/monaldi.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation treatment for COPD smokers: the role of counselling

Abstract: Smoking cessation is the only therapeutic intervention that can prevent COPD smokers from the chronic progression of their disorder. The most important intervention for helping these smokers to quit is a combination of counseling plus pharmacological treatment. The characteristics of the counseling should be different depending if this intervention is offered to smokers with a previous diagnosis of COPD or if the intervention is offered to smokers who have been recently diagnoses with COPD. The counseling of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…It is estimated that, in primary care, 25%–50% of patients with COPD are current smokers,5,9 a rate far behind the one in the present study. Nevertheless, only complete cessation of smoking slows the decline in lung function in COPD.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It is estimated that, in primary care, 25%–50% of patients with COPD are current smokers,5,9 a rate far behind the one in the present study. Nevertheless, only complete cessation of smoking slows the decline in lung function in COPD.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that in the long term, personal factors, such as self-confidence and nicotine dependence, as well as social support play a crucial role in the success of efforts to quit smoking. Patients who continue to smoke regardless of their severe lung disease are highly nicotine dependent and need more intensive strategies 9,10…”
Section: Discussionmentioning
confidence: 99%
“…Even more difficult is the approach to patients with COPD who, despite appropriate advice and counseling, do not quit. Jimenez Ruiz reviewed for us the pharmacological and counseling strategies to be used in these difficult cases [4,5].…”
mentioning
confidence: 99%